Diagnosis of intestinal and disseminated microsporidial infections in patients with HIV by a new rapid fluorescence technique. Issue 8 (August 1993) - van Gool, T; Snijders, F; Reiss, P; Eeftinck Schattenkerk, J K; van den Bergh Weerman, M A; Bartelsman, J F; Bruins, J J; Canning, E U; Dankert, J
Abstract : AIMS–To assess the value of a new rapid fluorescence method for the diagnosis of microsporidiosis in HIV seropositive patients. METHODS–Microsporidian spores in stools were demonstrated by using the fluorochrome stain Uvitex 2B. The new technique was evaluated in three groups of HIV seropositive patients with diarrhoea. Group 1: 19 patients with biopsy confirmed E bieneusi infection (186 stool samples); group 2: 143 consecutive patients from whom faeces were submitted for routine investigation of diarrhoea (318 samples); group 3: 16 patients with small intestinal biopsy specimens negative for microsporidia (55 samples). The new method was used to monitor spore shedding during experimental treatment with paromomycin and albendazole in four patients. RESULTS–Brightly fluorescent spores were detected in all stool samples of patients in group 1. In group 2 16 (11%) patients had spores in their stool samples. E bieneusi was found in 11 patients; in the other five another genus of microsporidia, Encephalitozoon, was recognised. Encephalitozoon spores were also found in the urine of three of these patients and in the maxillary sinus aspirate of two of them, suggesting disseminated infection. The results were confirmed by electron microscopic examination. In group 3 negative biopsy specimens were confirmed by negative stool samples in all cases. Treatment with albendazole and paromomycin did not affect the spore shedding in three patients with E bieneusi infection. By contrast, in a patient with Encephalitozoon sp infection albendazole treatment resulted in clinical improvement together with complete cessation of spore excretion in the stool. CONCLUSION–The Uvitex 2B fluorescence method combines speed, sensitivity, and specificity for the diagnosis and treatment evaluation of intestinal and disseminated microsporidiosis.